1. [ (9 * 5¹² - 5¹³) * 8 ] / 2 * 625 .......... = 289


2.( 3⁻¹,⁵ + 81⁻⁰,⁵ ) * ( 3⁻¹,⁵ - 3⁻² ) = ............ = 2/81


3. (25⁰,⁷⁵ + 625⁰,²⁵ ) * [ (0,2)⁻¹,⁵ - 25⁰,⁵ ] = .......... = 100


4. [ 2³ - ( 0,5)⁻¹,⁵ ] * [ ( 0,125 )⁻¹ + 2 √2 ] = ............ = 56


5. (343 ( do potęgi ⅓ ! ) - 7√ 7 ) * [ (1/7)⁻¹ + 7¹,⁵ ] = ...................... = - 294

2

Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-01-22T15:55:25+01:00
1. [ (9 * 5¹² - 5¹³) * 8 ] / 2 * 625 = 5¹²(9 - 5) * 8 / 2 * 5⁴ = 5¹²* 4 * 8 /2 * 5⁴ = 5⁸ * 2 * 8 = 5⁸ * 16
( już dziś było tego typu zadanie i też się wynik nie zgadzał:)


2.( 3⁻¹,⁵ + 81⁻⁰,⁵ ) * ( 3⁻¹,⁵ - 3⁻² ) = [3⁻¹,⁵ + (3⁴)⁻⁰,⁵] * ( 3⁻¹,⁵ - 3⁻² ) = (3⁻¹,⁵ + 3⁻²) * ( 3⁻¹,⁵ - 3⁻² ) = 3⁻³ - 3⁻³,⁵ + 3⁻³,⁵ - 3⁻⁴ = 3⁻³ - 3⁻⁴ = 1/3³ - 1/ 3⁴ = 1/27 - 1/81 = 3/81 - 1/81 = 2/81


3. (25⁰,⁷⁵ + 625⁰,²⁵ ) * [ (0,2)⁻¹,⁵ - 25⁰,⁵ ] = [(5²)⁰,⁷⁵ + (5⁴)⁰,²⁵ ] * [ (⅕)⁻¹,⁵ - (5²)⁰,⁵ ] = (5¹,⁵ + 5¹) * [(5⁻¹)⁻¹,⁵ - 5¹] = (5¹,⁵ + 5¹) * (5¹,⁵ - 5¹) = 5³ - 5²,⁵ + 5²,⁵ - 5² = 5³ - 5² = 125 - 25 =100


4. [ 2³ - ( 0,5)⁻¹,⁵ ] * [ ( 0,125 )⁻¹ + 2 √2 ] =[ 2³ - ( ½)⁻¹,⁵ ] * [ ( ⅛ )⁻¹ + 2 * 2¹/² ] = [ 2³ - (2⁻¹)⁻¹,⁵ ] * [ ( 1/2³ )⁻¹ + 2¹,⁵] = (2³ - 2¹,⁵) * [(2⁻³)⁻¹ + 2¹,⁵] = (2³ - 2¹,⁵) * (2³ + 2¹,⁵) = 2⁶ + 2⁴,⁵ - 2⁴,⁵ -2³ = 2⁶ - 2³= 64 - 8 = 56


5. (343^⅓ - 7√ 7 ) * [ (1/7)⁻¹ + 7¹,⁵ ] = [(7³)^⅓ - 7*7^½ ] * [ (7⁻¹)⁻¹ + 7¹,⁵ ] = (7 - 7¹,⁵)(7 + 7¹,⁵) = 49 + 7²,⁵ - 7²,⁵ - 7³ = 49 - 7³ = 49 - 343 = - 294
1 5 1
2010-01-22T16:28:48+01:00
1. -------


2.( 3⁻¹,⁵ + 81⁻⁰,⁵ ) * ( 3⁻¹,⁵ - 3⁻² ) = [3⁻¹,⁵ + (3⁴)⁻⁰,⁵] * ( 3⁻¹,⁵ - 3⁻² ) = (3⁻¹,⁵ + 3⁻²) * ( 3⁻¹,⁵ - 3⁻² ) = 3⁻³ - 3⁻³,⁵ + 3⁻³,⁵ - 3⁻⁴ = 3⁻³ - 3⁻⁴ = 1/3³ - 1/ 3⁴ = 1/27 - 1/81 = 3/81 - 1/81 = 2/81


3. (25⁰,⁷⁵ + 625⁰,²⁵ ) * [ (0,2)⁻¹,⁵ - 25⁰,⁵ ] = [(5²)⁰,⁷⁵ + (5⁴)⁰,²⁵ ] * [ (⅕)⁻¹,⁵ - (5²)⁰,⁵ ] = (5¹,⁵ + 5¹) * [(5⁻¹)⁻¹,⁵ - 5¹] = (5¹,⁵ + 5¹) * (5¹,⁵ - 5¹) = 5³ - 5²,⁵ + 5²,⁵ - 5² = 5³ - 5² = 125 - 25 =100


4. [ 2³ - ( 0,5)⁻¹,⁵ ] * [ ( 0,125 )⁻¹ + 2 √2 ] =[ 2³ - ( ½)⁻¹,⁵ ] * [ ( ⅛ )⁻¹ + 2 * 2¹/² ] = [ 2³ - (2⁻¹)⁻¹,⁵ ] * [ ( 1/2³ )⁻¹ + 2¹,⁵] = (2³ - 2¹,⁵) * [(2⁻³)⁻¹ + 2¹,⁵] = (2³ - 2¹,⁵) * (2³ + 2¹,⁵) = 2⁶ + 2⁴,⁵ - 2⁴,⁵ -2³ = 2⁶ - 2³= 64 - 8 = 56


5. (343^⅓ - 7√ 7 ) * [ (1/7)⁻¹ + 7¹,⁵ ] = [(7³)^⅓ - 7*7^½ ] * [ (7⁻¹)⁻¹ + 7¹,⁵ ] = (7 - 7¹,⁵)(7 + 7¹,⁵) = 49 + 7²,⁵ - 7²,⁵ - 7³ = 49 - 7³ = 49 - 343 = - 294
1 1 1